Behandlung von Kindern mit schwerer Hämophilie A und Inhibitoren: eine gesundheitsökonomische Evaluation für Deutschland - Berger, K.; Schopohl, D.; Eheberg, D.; Auerswald, G.; Kurnik, K.; Schramm, W. (Klinische Pädiatrie, 2013)
Decision makers request increasingly for high levels of evidence when allocating resources in medical care. This is hardly feasible for rare diseases. The objective was to analyze clinical and economic aspects of different immune tolerance induction (ITI) strategies for children with severe haemophilia A and inhibitors.A decision model, time frame 18 years (base case: 2 year old boy), was constructed from a German statutory health insurance (SHI) perspective. Compared were high-dose (HD) ITI, low-dose (LD) ITI, ‘ITI with risk assessment’, on-demand (OD) treatment with bypassing agents. Clinical data were derived from structured literature research and expert opinion. Sensitivity analyses were conducted for parameters with wide statistical ranges.Base case analysis: total costs for HD ITI amounted to €3.4 million with 40.9% ITI costs, 51 joint bleeds, 36 hospital days; LD ITI, €2.4 million with 21.4% ITI costs, 74 joint bleeds, 52 hospital days; ‘ITI with risk assessment’, €2.7 million with 27.6% ITI costs, 53 joint bleeds, 37 hospital days; OD treatment, €1.7 million, 146 joint bleeds, 104 hospital days. Incremental costs per bleed avoided with HD ITI decreased from €1 million to €0.15 million with increase of joint bleeds from 3 to 20 per year, when compared to ‘ITI with risk assessment’ in sensitivity analysis.‘ITI with risk assessment’ is cost-saving with comparable outcomes to HD ITI. However, patient-related factors like bleeding frequency have to determine treatment decisions in individual patients. More clinical data is needed to increase the significance of model calculations.
Keywords: costs; haemophilila A; inhibitors; immune tolerance induction; ITI; outcome